The Palestinian issue an overview - Ziad Mohammad; Mohsen Saleh, Dr.; Salim Faisal (Kuala Lumpur: Professional Eagle Trading Sdn. Bhd., 2003)
An organized presentation which is covers the main aspects of the Palestinian issue, land, peoples, zionism and the Zionist State, Arab-Israel War, Palestinian resistance and peace projects and settlement
Manager and editor, Dr. Mohsen Saleh ; designer and programmer, Salim Faisal
System requirements: Microsoft windows 98 or above, Pentium II processor or its equivalent, 120 MB free hard disk space, 12 X CD-ROM.
Keywords: Arab-Israeli conflict; Palestinian Arabs -- Israel